Web-Based Job Vacancies Provider Application in the NTB Region Using the Laravel And Mysql Framework - Baiq Ayu Indah Wardaningsih; Amri Muliawan Nur; Imam Fathurrahman (Fakultas Teknik Universitas Hamzanwadi, 2022)
This research is motivated by employment that tends to be difficult when looking for work in companies. In other words, applicants still use the usual methods to find information about job vacancies. They go to companies to look at job vacancies notice boards, and look in print media such as newspapers, magazines, brochures, or person-to-person information. Companies that want to open job vacancies also do the same thing. This method has the disadvantage that it is not effective and efficient, because it requires time and money. Therefore, this researcher built a web-based job vacancy provider system using the waterfall model with observation data collection techniques and literature study. This will increase effectiveness in finding work according to their respective fields or abilities. The purpose of this system is to provide convenience for job seekers and companies. Job seekers can obtain job search information online, companies can provide job search information through the website and assist companies in finding prospective applicants according to the desired criteria. From this research, it produces information on web-based job vacancies equipped with a search menu for the desired vacancy category